Effects of Sleep Quality on Imagery Ability in Athletic Populations. (June 2018) - Shearer, David; Bruton, Adam; Short, Sandra; Roderique-Davies, Gareth
This study explored the relation between athletes' sleep quality and imagery ability. A total of 201 athletes (39.3% female, 60.7% male; M age  = 23.28 years, SD  = 6.00) completed the Sport Imagery Ability Questionnaire and the Pittsburgh Sleep Quality Index. Simple regression analyses revealed that global sleep quality predicted affect imagery ability. Multiple regression analyses revealed that daytime dysfunction predicted global imagery ability as well as skill, strategy, affect, and mastery imagery ability dimensions. In addition, use of sleeping medication predicted global imagery ability, as well as goal and affect imagery ability dimensions. Results provide some support for Cumming and Williams' revised applied model of deliberate imagery use, suggesting that individual factors influence the effectiveness of imagery use. Specifically, athletes who have no disruption to daily functioning due to sleep find it easier to image sport-related content.